Pharmacokinetic and clinical comparison of super-bioavailable itraconazole and conventional itraconazole at different dosing in dermatophytosis - Dhiraj Dhoot; Gaurav Kumar Jain; Mukesh Manjhi; Prashant Kesharwani; Namrata Mahadkar; Hanmant Barkat (BioExcel Publishing Ltd, 2023)
Background: Due to changing face of dermatophytosis in India, many dermatologists practice different dosing patterns of itraconazole (ITZ). Recently, a new form of ITZ, super-bioavailable ITZ (SBITZ), has been commercialized to overcome the pharmacokinetic challenges of conventional ITZ (CITZ). Serum and sebum concentration of ITZ plays an important role in the management of dermatophytosis. Hence, the current study compares the rate and extent of serum and sebum concentration of SBITZ and CITZ at different dosing to determine their efficacy and safety in patients with dermatophytosis. Methods: This was an open-label, randomized, fourarm study including 40 adult patients diagnosed with glabrous tinea who were randomized equally into four groups to receive either CITZ-100-BD or CITZ-200-OD (2×100 mg capsules) or SBITZ-130-OD or SBITZ-100-OD (2×SBITZ-50 mg capsules) for 4 weeks. Serum and sebum samples were analysed at different time intervals along with clinical efficacy and safety. Results: For serum concentration, on day 28, the arithmetic mean and standard deviation (SD) for CITZ- 100-BD, CITZ-200-OD, SB-130-OD and SB100-OD were 1262±233.5 ng/mL, 1704±261.6 ng/mL, 1770±268.9 ng/mL and 1520±231.7 ng/mL, respectively, which was statistically significant for OD dosing of ITZ/SBITZ over CITZ-100- BD. Similarly, for sebum concentration, the arithmetic mean and SD for CITZ-100-BD, CITZ-200-OD, SB-130-OD and SB-100-OD were 1042±163.45 ng/mg, 1423±192.46 ng/ mg, 1534±227.55 ng/mg and 1107±182.35 ng/mg, respectively, which was statistically significant for SB-130-OD and CITZ-200-OD over CITZ-100-BD and SBITZ-100-OD dosing. No significant difference was noted between SBITZ-130 and CITZ-200 (p=0.25). Only two patients achieved complete cure in the SBITZ-130 group, whereas no patients achieved the same in other groups (p=0.47). All the dosages were very well tolerated with only 12 adverse events reported by ten patients in all groups. Conclusion: All formulations achieved desired serum and sebum concentrations required for efficacy in dermatophytosis, but SB 130 mg OD and CITZ 200 mg OD were statistically significant than other ITZ doses in achieving sebum concentration. Additionally, SBITZ 130 mg OD was bioequivalent to CITZ 200 mg OD and achieved similar results to those of CITZ 200 mg OD but at 35% lower drug concentrations.